Exploring the Beneficial Effects of Guangxi Longevity Dietary Patterns on Human Body Based on Metabolomics - Kunchen HAN; Wenjun ZHU; Haiyan ZHAO; Qianzu HE; Jinke MA; Xiaohan YU; Qinren ZHANG; Quanyang LI (Shipin gongye ke-ji, 2022)
To explore the relationship between diet and human health, this study aimed to evaluate the beneficial effects of the existing Guangxi longevity dietary pattern on the human body from metabolomics. After 2 weeks of habitual diet, the selected volunteers followed this dietary pattern with high adherence for the same period. The blood and fecal samples were collected 3 times then performed metabolomics analysis, including before the habitual diet, the beginning (which was also the ending point of habitual diet) and the end of Guangxi longevity dietary pattern. The results showed that after the Guangxi longevity dietary intervention of volunteers, the relative abundance of serum histidine, glycerol, α-glucose and β-glucose was significantly increased (P<0.05), but the relative richness of choline and lactic acid reduced obviously (P<0.05). In addition, the fecal acetate and butyrate increased apparently (P<0.05). Moreover, the analysis of metabolome enrichment and pathway revealed that these metabolites' variations might be closely related to three pathways, including glycolysis/gluconeogenesis pathway, pyruvate metabolism, and galactose metabolism. Through the analysis of differential metabolites, it was considered that Guangxi longevity dietary pattern played a promoted role in improving the level of inflammation, regulating the health status and preventing the organism from developing cardiovascular diseases. The above results also provide a mechanical explanation of the relationship between dietary patterns and healthy longevity from human metabolism.